Conversion of Dexon (p-Dimethylaminobenzenediazo Sodium Sulfonate) to N,N-Dimethyl-p-Phenylenediamine by Pseudomonas fragi Bk9 - Karanth, N. G. K. (1974)
The metabolism of the fungicide Dexon (p-dimethylaminobenzenediazo sodium sulfonate) by a soil bacterium is reported for the first time. The organism which is capable of using Dexon only by a co-metabolic process was obtained by enrichment culture and was identified as Pseudomonas fragi. The first metabolic product of Dexon was identified as N,N-dimethyl-p-phenylenediamine. The presence of an enzyme, p-dimethylaminobenzenediazo sodium sulfonate reductase, capable of reducing Dexon to N,N-dimethyl-p-phenylenediamine has been demonstrated in the cell-free extracts of the organism. The enzyme is found to be in the soluble fraction and requires dithiothreitol as a reductant.